Mechanical properties of thermoplastic natural rubber (TPNR) reinforced with different types of carbon nanotube - Mou’ad A. Tarawneh,; Sahrim Hj. Ahmad,; Rozaidi Rasid,; Yahya .S.Y,; Shamsul Bahri A. R,; Seyong Ehnoum,; Ku Zarina Ka,; Lee, Yip Seng (Universiti Kebangsaan Malaysia, 2011)
The effect of various multi-walled carbon nanotubes (MWNTs) on the tensile properties of thermoplastic natural rubber (TPNR) nanocomposite was investigated. The nanocomposite was prepared using melt blending method. MWNTs were added to improve the mechanical properties of MWNTs/TPNR composites in different compositions of 1, 3, 5, and 7 wt.%. The results showed that the mechanical properties of nanocomposites were affected significantly by the composition and the properties of MWNTs. SEM micrographs confirmed the homogenous dispersion of MWNTs in the TPNR matrix and promoted strong interfacial adhesion between MWNTs and the matrix which was improved mechanical properties significantly